Osmotic Shifts, Cerebral Edema, and Neurologic Deterioration in Severe Hepatic Encephalopathy. Issue 2 (February 2018) - Liotta, Eric Michael; Romanova, Anna L.; Lizza, Bryan D.; Rasmussen-Torvik, Laura J.; Kim, Minjee; Francis, Brandon; Sangha, Rajbeer Singh; Carroll, Timothy J.; Ganger, Daniel; Ladner, Daniela P.; Naidech, Andrew M.; Paparello, James J.; et al.
Abstract : Objectives: We sought to determine the effect of acute electrolyte and osmolar shifts on brain volume and neurologic function in patients with liver failure and severe hepatic encephalopathy. Design: Retrospective analysis of brain CT scans and clinical data. Setting: Tertiary care hospital ICUs. Patients: Patients with acute or acute-on-chronic liver failure and severe hepatic encephalopathy. Interventions: Clinically indicated CT scans and serum laboratory studies. Measurements and Main Results: Change in intracranial cerebrospinal fluid volume between sequential CT scans was measured as a biomarker of acute brain volume change. Corresponding changes in serum osmolality, chemistry measurements, and Glasgow Coma Scale were determined. Associations with cerebrospinal fluid volume change and Glasgow Coma Scale change for initial volume change assessments were identified by Spearman's correlations ( r s ) and regression models. Consistency of associations with repeated assessments was evaluated using generalized estimating equations. Forty patients were included. Median baseline osmolality was elevated (310 mOsm/Kg [296–321 mOsm/Kg]) whereas sodium was normal (137 mEq/L [134–142 mEq/L]). Median initial osmolality change was 9 mOsm/kg (5–17 mOsm/kg). Neuroimaging consistent with increased brain volume occurred in 27 initial assessments (68%). Cerebrospinal fluid volume change was more strongly correlated with osmolality ( r = 0.70; p = 4 × 10 –7 ) than sodium ( r = 0.28; p = 0.08) change. Osmolality change was independently associated with Glasgow Coma Scale change ( p = 1 × 10 –5 ) and cerebrospinal fluid volume change ( p = 2.7 × 10 –5 ) in initial assessments and in generalized estimating equations using all 103 available assessments. Conclusions: Acute decline in osmolality was associated with brain swelling and neurologic deterioration in severe hepatic encephalopathy. Minimizing osmolality decline may avoid neurologic deterioration. Abstract : Supplemental Digital Content is available in the text.